Todor Pavlović’s social ideas - Kajtez, Ilija; Starčević, Srđan (Sociološki pregled, 2021)
The paper analyzes the sociological works of Todor Pavlović, with the aim of presenting his basic social ideas and checking the relevance of his conclusions about the relationship between social development and military organization. A special focus is placed on Pavlović’s explanation of the development of military organization, within which the position of dialectical materialism about the influence of war technique on army organization and tactics is refuted. This sets Pavlović apart from other Serbian and Yugoslav sociologists of the 20th century who studied the army, and anticipates new sociological views on the relationship between technical achievements and the organization of social processes. Basic analytical and synthetic methods, content analysis as well as biographical and comparative methods were used.